Colonising the Female Mind and Space through Colonial Pedagogy in India, 1880 to 1920s - Preeti,; Mishra, Abhinav (JOURNAL OF INDIAN EDUCATION, 2022)
This article articulates how colonial education of women was designed for them to be a cog in the patriarchal machinery. Women were not seen as professionals; instead, they were to get educated enough to fit in the new middle class households where they could administer their chores effectively and raise kids according to the new set standards. Curriculum for the upper caste middle class women got doubly colonised— it was a composite mixture of the Brahmanical code of conduct taking cues from the British patriarchy. Gender was presented on a binary model rather than in an intersectional way. This article traces the gendered dynamics in pedagogical spaces— power and authority— in teaching approaches. Discussing women like Pandita Ramabai, among the lone voices of dissent, this article will argue that albeit the percentage of women educated was far less than the men, yet they had a far-reaching effect on the society, especially the urban society.